Food processing - a viable industry in Malaysia. - Abdul Karim, Mohamed Ismail; Mohd. Zain, Asiah; Bakar, Jamilah (1986)
Malaysia presently import M$3.3 billion worth of food. If steps are not taken to step up food production, the import bill might go up to M$3.8 billion and M$4.2 billion by 1990 and 1995, respectively. With the implementation of the Agriculture Policy and the Industrial Master Plan, the goverment had given top priority towards expanding the agricultural and food sector. Also with the present declining prices in primary commodity, and the gloomy outlook in the manufacturing, property and mining sector, many corporate giants are turning towards food production as alternate sources of investment. There is a great demand for fresh and processed food both for the domestic and foreign market. Various aspect of food processing and their prospect as viable industry in Malaysia are being discussed in this paper.